2019
DOI: 10.1063/1.5086534
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic mixed convection flow of Jeffery fluid with thermophoresis, Soret and Dufour effects and convective condition

Abstract: The aim of this paper is to investigate heat and mass transfer of Jeffery fluid on a stretching sheet. Moreover, the influence of magnetic field with mixed convection, convective boundary condition and Soret and Dufour effects is also brought into the consideration along with chemical reaction and thermophoresis condition. The problem is modeled by system of partial differential equations and solutions are obtained by optimal homotopy analysis method. In addition, for comprehensive interpretation of the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Considering the associated boundary conditions, the assumed solutions can be expressed as Applying assumed solutions (14) to Eqs. (10)- (13) and equating the terms, harmonic and non-harmonic, gives (8)…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the associated boundary conditions, the assumed solutions can be expressed as Applying assumed solutions (14) to Eqs. (10)- (13) and equating the terms, harmonic and non-harmonic, gives (8)…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…It was reported that a rise in Soret and Dufour increases the skin friction. Iftikhar et al [8] studied mixed convection MHD Jeffery fluid flow in the presence of Soret, Dufour and thermophoresis. The resulted partial differential equations are solved using Optimal Homotopy Analysis Method (OHAM).…”
mentioning
confidence: 99%
“…Research such as that done by Saqib et al [6] and Anwar et al [7] have specifically looked at the application of AB fractional derivatives in channel flow through porous media and the fractional order Oldroyd-B fluid flow model in channels under generalized boundary conditions. Further applications can be found in References [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On a Micropolar nanofluid flow, Ibrahim et al 25 investigated the impact of the Soret and Dufour factor with multiple slip conditions past a bidirectional surface. The characteristic of heat and mass transfer on a mixed convective Jeffery fluid flow over a bidirectional stretchable sheet amalgamated with Soret–Dufour effect and chemical reaction is examined by Iftikhar et al 26 . Significant researches in this direction are mentioned in Refs.…”
Section: Introductionmentioning
confidence: 99%